Female Primary School Teachers' Participation in Informal Financial Groups and its Implications for Teaching Performance - Juma, Madina Hamisi; Mpuya, Grace; Churk, Josephine (Indonesian Journal of Social Research (IJSR), 2024)
Teachers are reported to be constrained by financial problems like low salaries, which may negatively affect their teaching performance. Informal financial groups (IFGs) emerged as financial intermediaries, like teachers, to help individuals with financial issues. However, informal financial groups reported being connected to many challenges, including stress and conflicts, thus negatively affecting teaching performance. The proposed research aimed at understanding the implications of informal financial group participation on the teaching performance of female primary school teachers in Dodoma City, Tanzania. The study focused on a population of 63 female primary school teachers, with data collected from 34 respondents through surveys and interviews. Data analysis was employed and analyzed using SPSS and conventional content analysis. The study results were analyzed using descriptive and regression analysis for Quantitative data and content analysis for qualitative data. The findings revealed that female primary school teachers' participation in IFGs does not significantly implicate their teaching performance. Also, the findings show that IFGs are primarily used to secure social support during unexpected events and generate extra income to meet household needs not covered by teachers' low salaries. The study provided discourse on decent financial inclusion that positively impacts work performance, such as that of teachers. The findings inform policymakers to review teachers’ remuneration to sufficiently support their livelihoods to enable them to focus on teaching activities.